2017
DOI: 10.1021/jacs.7b05184
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Photoelectrochemical Oxidation of Methanol on Hematite Photoanodes

Abstract: The kinetics of photoelectrochemical (PEC) oxidation of methanol, as a model organic substrate, on α-Fe2O3 photoanodes are studied using photoinduced absorption spectroscopy and transient photocurrent measurements. Methanol is oxidized on α-Fe2O3 to formaldehyde with near unity Faradaic efficiency. A rate law analysis under quasi-steady-state conditions of PEC methanol oxidation indicates that rate of reaction is second order in the density of surface holes on hematite and independent of the applied potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 37 publications
3
110
0
Order By: Relevance
“…Ling et al further revealed that the internal mechanism of Sn doping could be achieved at a relatively low temperature (i.e., 650°C) [22]. However, most reports used diffusion or nonquantitative method to introduce additive elements because few preparation technologies could quantitatively introduce dopant in spite of many methods being developed for growing α-Fe 2 O 3 , such as atomic layer deposition (ALD) [23], atmospheric pressure chemical vapor deposition (APCVD) [24], electro-chemical deposition [25], pyrolysis [26], and hydrothermal methods [27]. Non-quantitative analysis cannot exactly discover the change in crystallinity and composition as the doping density changes.…”
Section: Introductionmentioning
confidence: 99%
“…Ling et al further revealed that the internal mechanism of Sn doping could be achieved at a relatively low temperature (i.e., 650°C) [22]. However, most reports used diffusion or nonquantitative method to introduce additive elements because few preparation technologies could quantitatively introduce dopant in spite of many methods being developed for growing α-Fe 2 O 3 , such as atomic layer deposition (ALD) [23], atmospheric pressure chemical vapor deposition (APCVD) [24], electro-chemical deposition [25], pyrolysis [26], and hydrothermal methods [27]. Non-quantitative analysis cannot exactly discover the change in crystallinity and composition as the doping density changes.…”
Section: Introductionmentioning
confidence: 99%
“…As reference values, we note that Wahl et al . reported a faradaic efficiency of 30 % for the oxidation of methanol over rutile electrodes, while Mesa et al . showed a faradic efficiency of 96 % for the same reaction over hematite electrodes.…”
Section: Discussionmentioning
confidence: 87%
“…Charge transfer efficiencies can be determined from photoelectrochemical impedance spectroscopy (PEIS) data, 29,48 transient absorption spectroscopy (TAS) 49,50 or intensity modulated photocurrent spectroscopy (IMPS), 51 but these complicate the Gärtner-Butler method of at band determination substantially. Alternatively, addition to the electrolyte of sacricial reagents such as hydrogen peroxide, 52 hydrogen sulde 53 or methanol, 54 can increase dramatically the rates of charge transfer relative to those of recombination. This approach could increase condence in the at band potential value determined from eqn (10).…”
Section: Methods For At Band Determinationmentioning
confidence: 99%